How to (ab)use a COVID-19 antigen rapid test with soft drinks?. (October 2021) - Velavan, Thirumalaisamy P; Pallerla, Srinivas Reddy; Kremsner, Peter G
Abstract: With reasonably good specificity and sensitivity, the speed and convenience of COVID-19 antigen tests have led to self-testing in schools, offices, and universities in the European Union (EU). Although self-testing can be beneficial and increase the accessibility to testing, there are potential ways to confound a positive COVID-19 lateral flow test. We observed that all soft drinks, energy drinks, alcoholic beverages (vodka, whiskey, and brandy), commercially bottled mineral water, and carbonated mineral water caused the appearance of a red test line. However, when equal volumes of the buffer and the respective beverages are mixed, there are no false-positive test lines. Deceitful methods may easily lead to misuse of COVID-19 antigen rapid tests and lead to false-positive results; however, this does not prove that these tests are unreliable when performed correctly.